Next decade of telecommunications artificial intelligence - Ye OUYANG; Lilei WANG; Aidong YANG; Maulik SHAH; David BELANGER; Tongqing GAO; Leping WEI; Yaqin ZHANG (Dianxin kexue)
It has been an exciting journey since the mobile communications and AI were conceived 37 years and 64 years ago.While both fields evolved independently and profoundly changed communications and computing industries, the rapid convergence of 5G and AI is beginning to significantly transform the core communication infrastructure, network management and vertical applications.The individual roadmaps of mobile communications and artificial intelligence in the early stage were firstly outlined, with a concentration to review the era from 3G to 5G when AI and mobile communications started to converge.With regard to telecommunications artificial intelligence, the progress of AI in the ecosystem of mobile communications was further introduced in detail, including network infrastructure, network operation and management, business operation and management, intelligent applications towards BSS ＆amp; OSS convergence, verticals and private networks etc.Then the classifications of AI in telecom ecosystems were summarized along with its evolution paths specified by various international telecommunications standardization bodies.Towards the next decade, the prospective roadmap of telecommunications artificial intelligence was forecasted.In line with 3GPP and ITU-R’s timeline of 5G ＆amp; 6G, the network intelligence following 3GPP and O-RAN routes, experience and intention driven network management and operation, network AI signaling system, intelligent middle-office based BSS, intelligent customer experience management and policy control driven by BSS＆amp; OSS convergence, evolution from SLA to ELA, and intelligent private network for verticals were further explored.It concludes that with the vision AI will reshape the future B5G/6G landscape, and we need fully take the unprecedented opportunities.